2004
DOI: 10.1111/j.1439-0442.2004.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycosis in a One‐humped Camel (Camelus dromedarius)

Abstract: An actinomycotic granuloma caused by Actinomyces viscosus is reported in a dromedary camel. Two hard, cutaneous, large granulamatous nodules were present on both sides of the postero-ventral side of the mandible exhibiting exudation and necrosis. After radical excision of the lesion, the daily treatment with penicillin-streptomycin combination was continued for 4 weeks. About 8 and 24 weeks from the initial treatment, no new nodules were noticed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…are actinomycosis (Kilic & Kirkan, 2004), anthrax (Musa, Shomein, Abd el Razig, Meki, & Hassan, 1993), borreliosis (Helmy, 2000), chlamydiosis (Elzlitne & Elhafi, 2016), clostridial diseases (Wernery, Ul-Haq, Joseph, & Kinne, 2004;Younan & Gluecks, 2007), balantidiasis (Tajik, Farda, paidar, Anousheh, & Dehghani, 2013), melioidosis (Bergin & Torenbeeck, 1991), Staphylococcus aureus (Jaradat, Al Aboudi, Shatnawi, & Ababneh, 2013), Corynebacterium ulcerance (Tejedor, Martin, Lupiola, & Gutierrez, 2000), mycoplasma (Mederos-Iriarte et al, 2014), streptococcal (Heller, Anderson, & Silveira, 1998), trypanosomiasis (Bennoune, Adili, Amri, Bennecib, & Ayachi, 2013), fascioliasis (Haridy & Morsy, 2000), schistosomiasis (Singh, Borah, Dadhich, & Sharma, 2013), sarcopticosis (Sk, Tuteja, & Sena, 2009), hepatitis (Woo et al, 2014), influenza A virus (Yamnikova et al, 1993), rift valley fever (Swai & Sindato, 2015), West Nile fever (El-Harrak et al, 2011) (Wernery, Kinne, & Schuster, 2014). Some of these diseases are very common in camels, while others are rare.…”
mentioning
confidence: 99%
“…are actinomycosis (Kilic & Kirkan, 2004), anthrax (Musa, Shomein, Abd el Razig, Meki, & Hassan, 1993), borreliosis (Helmy, 2000), chlamydiosis (Elzlitne & Elhafi, 2016), clostridial diseases (Wernery, Ul-Haq, Joseph, & Kinne, 2004;Younan & Gluecks, 2007), balantidiasis (Tajik, Farda, paidar, Anousheh, & Dehghani, 2013), melioidosis (Bergin & Torenbeeck, 1991), Staphylococcus aureus (Jaradat, Al Aboudi, Shatnawi, & Ababneh, 2013), Corynebacterium ulcerance (Tejedor, Martin, Lupiola, & Gutierrez, 2000), mycoplasma (Mederos-Iriarte et al, 2014), streptococcal (Heller, Anderson, & Silveira, 1998), trypanosomiasis (Bennoune, Adili, Amri, Bennecib, & Ayachi, 2013), fascioliasis (Haridy & Morsy, 2000), schistosomiasis (Singh, Borah, Dadhich, & Sharma, 2013), sarcopticosis (Sk, Tuteja, & Sena, 2009), hepatitis (Woo et al, 2014), influenza A virus (Yamnikova et al, 1993), rift valley fever (Swai & Sindato, 2015), West Nile fever (El-Harrak et al, 2011) (Wernery, Kinne, & Schuster, 2014). Some of these diseases are very common in camels, while others are rare.…”
mentioning
confidence: 99%
“…In this case, it appears most probable that the camel became infected BPV‐1 from exposure to cattle. It has previously been reported 12 that actinomycosis could be seen in camel housed with cattle in this region.…”
Section: Discussionmentioning
confidence: 80%
“…Some references may describe tooth root abscesses or similar infections, but the exact etiology of the case may be unclear. One case from 2004 identifies Actinomyces viscous in a dromedary camel presenting as bilateral mandibular exudation and necrosis [ 5 ]. The lesion was excised, and the camel was treated with 4 weeks of penicillin-streptomycin, with no progression noted at 24 weeks postoperatively [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…One case from 2004 identifies Actinomyces viscous in a dromedary camel presenting as bilateral mandibular exudation and necrosis [ 5 ]. The lesion was excised, and the camel was treated with 4 weeks of penicillin-streptomycin, with no progression noted at 24 weeks postoperatively [ 5 ]. A study of 61 cases of wounds to the head and neck of dromedary camels identified 8.2% ( n = 5) with submandibular abscesses but was not specific to the agent or bony structure involvement [ 6 ].…”
Section: Discussionmentioning
confidence: 99%